LEGAL STANDING OF THE FOREST AREA OCCUPATION BOUNDARY REPORT IN PROVING LAND OWNERSHIP DISPUTES - Hadi Prabowo; Imam Koeswahyono; Iwan Permadi (RADJA PUBLIKA, 2023)
The legal position of the Minutes of Boundary Documents contains many legal instruments against the state's right to control over forest areas, but this is often misunderstood, causing legal uncertainty, especially the legal position in the trial of proving ownership, for this Minutes of Boundary Demarcations need to be studied further, especially regarding certainty and classification. evidence in civil procedural law. This research is a normative juridical research, using a statutory approach. The conclusions that can be drawn from this research are, firstly, the existence of Minutes of Boundary Demarcation is not merely authentic evidence but an instrumental constitutional authority for the state to control forest areas, and contains three aspects, juridical, historical and sociological.